Exploration of Titanium-Based Fine-Particle Additive Influence on Cohesive and Adhesive Strength Enhancement in Epoxy-Polymer Composites - Baranovska, Oksana; Bagliuk, Gennadii; Buketov, Andriy; Sapronov, Oleksandr; Baranovsky, Dmytro (Physics and Chemistry of Solid State, 2024)
The study examines how the inclusion of a dispersed powder filler affects the physico-mechanical properties of an ultrasound-modified epoxy matrix. Varying the filler content from 5% to 60% by weight in the composite revealed an optimal concentration for enhanced mechanical properties. Introducing the filler at 5% led to maximum impact strength (W = 18.47 kJ/m2) and minimized destructive stresses during bending (σB = 51.75 MPa). At 10% filler concentration, destructive bending stresses increased significantly from σB = 48.0 MPa to σB= 74.85 MPa, with impact strength improving from W = 7.4 kJ/m2 to W = 17.42…18.47 kJ/m2. Further increasing filler content to 20–60% resulted in a slight decrease in destructive stresses while still surpassing for the filler-free epoxy matrix strength. Optimal modifier content improved adhesive characteristics, achieving a peak adhesive strength (σa = 33.4 MPa) at 20% filler, albeit with residual stresses at 0.34 MPa. Introducing the modifier at 10% increased adhesive strength to σa = 28.6 MPa, marking a 1.15-fold improvement over the filler-free epoxy matrix, while reducing residual stresses from σres = 1.4 MPa to σres = 1.0 MPa. Higher filler content (40-60%) led to decreased adhesive strength and increased residual stresses (σres = 0.62…0.69 MPa).